Effectual Algorithm for Avoidance of Version Number Attacks in Internet of Things (IoT) - Esraa Saleh Alomari, Dr. (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) is one of the emerging domains in the wireless communication and technologies whereby the sensor based devices interact with each other using radio frequencies. The enormous work is going on in this segment to enrich the security still there is huge scope of research. In IoT, the implementations of Vehicular Adhoc Networks (VANET), Internet of Vehicles (IoV), Smart Offices, Smart Cities are quite prominent which are addressed in this research work. With the use of soft computing approaches, the implementation of higher degree of security can be done. "In this research manuscript, the approach to integrate the dynamic key exchange with the Elephant Herd Optimization (EHO) is presented to achieve the higher degree of energy optimization and overall lifetime of the network communication. The key concept of the cluster head shuffling using EHO and inner modules of key exchange are simulated in Contiki-Cooja that is open source simulator for advance wireless networks". But the version number attacks can destroy the overall scenario and the performance in which the exploitation of multiple resources can be done. In this research work, the approach to defeat and push back the version number attacks in RPL using dynamic security is implemented and evaluated on multiple parameters.Â Â Â